Handbook of aging and the social sciences - Binstock, Robert H.; George, Linda (Handbooks of aging., 2011)
The Handbook of Aging and the Social Sciences, Seventh Edition summarizes the research literature on the social aspects of aging. The Seventh Edition will have 88% new material and authors with 25 chapters: 22 of the chapters will be on completely new topics. Separated into four sections, the fully revised handbook will cover Theory and Methods, Aging and Social Structure, Social Factors and Social Institutions, and Aging and Society. Contains all the main areas of social science gerontological research in one volume Begins with a section on theory and methods Edited by one of the fathers of gerontology (Binstock) and contributors represent top scholars in gerontology.